Bacterial vaginosis and the risk of Trichomonas vaginalis acquisition among HIV-1 negative women - Balkus, Jennifer E. (2014)
BACKGROUND: The vaginal microbiota may play a role in mediating susceptibility to sexually transmitted infections, including Trichomonas vaginalis (TV). METHODS: Data were analyzed from HIV-1 seronegative women participating in HIV Prevention Trials Network Protocol 035. At quarterly visits for up to 30 months, participants completed structured interviews and specimens were collected for genital tract infection testing. TV was detected by saline microscopy. BV was characterized by Gram stain using the Nugent score (BV=7-10; intermediate=4-6; normal=0-3 [reference group]). Cox proportional hazards models stratified by study site were used to assess the association between Nugent score category at the prior quarterly visit and TV acquisition. RESULTS: In this secondary analysis, 2,920 participants from Malawi, South Africa, USA, Zambia and Zimbabwe contributed 16,259 follow-up visits. BV was detected at 5,680 (35%) visits and TV was detected at 400 (2.5%) visits. Adjusting for age, marital status, hormonal contraceptive use, unprotected sex in the last week and TV at baseline, intermediate Nugent score and BV at the prior visit were associated with an increased risk of TV (intermediate score: adjusted hazard ratio [aHR]=1.73, 95% confidence interval [CI] 1.21-2.19; BV: aHR=2.40, 95% CI 1.92-3.00). Sensitivity analyses excluding 211 participants with TV at baseline were similar to those from the full study population (intermediate score: aHR=1.54, 95% CI 1.10-2.14; BV: aHR=2.23, 95% CI 1.75-2.84) CONCLUSIONS: Women with a Nugent score >3 were at an increased risk of acquiring TV. If this relationship is causal, interventions that improve the vaginal microbiota could contribute to reductions in TV incidence.